INFLUENCE OF A NEW MARINATION METHOD ON THE ORGANOLEPTIC INDICATORS OF BEEF STEAKS - BATRACHENKO, OLEXANDR; OREL, VICTOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Fried steaks are a popular dish. The reason for this is the high taste and high nutritional value of such a dish. We are talking, first of all, about beef steaks, which, as is known, are divided into classic and alternative. Improving the taste of alternative steaks and increasing their tenderness is achieved by marinating. At the same time, classic steaks can also be marinated in order to give them original flavors. At the same time, there are two main methods of wet marinating of meat raw materials: immersing the raw materials in the marinade for a long time (usually 6-12 hours) and injecting the marinade into the pieces of raw materials. Both of them have significant drawbacks. The aim of the work is to substantiate a new method of intensifying the marinating of meat raw materials and to study its effect on the organoleptic characteristics of beef steaks. The object of the study is the processes of marinating meat raw materials. The subject of the study is the regularities of the influence of a new method of intensifying the marinating of meat raw materials on the quality of the resulting finished product. A new method of intensifying the marinating of meat raw materials was developed. Its distinctive feature is that before immersing the meat in the marinade, tubular elements are introduced into the meat, one end of which is pointed. Moreover, they are introduced in such a way that their outlet holes are located in the middle of the thickness of the piece of meat. This creates marinating channels through which the marinade gets the opportunity to get inside the piece of meat by gravity. It was established that steaks that were marinated for 30 minutes using tubular elements were no worse than the control sample in all organoleptic parameters that were taken into account. Of particular interest are the results of the organoleptic analysis of the sample that was marinated for 45 minutes using tubular elements. Its organoleptic parameters turned out to be noticeably better than those of the control sample. The organoleptic indicators of the sample that underwent the vacuuming operation are interesting. In general, it was found that the use of tubular elements, which are introduced into the meat raw material in the above-mentioned manner before its marinating, allows to significantly reduce the duration of the marinating process (up to 2 times), while ensuring the specified high quality of the product. The developed solution was granted a patent of Ukraine for a utility model No. 158013 dated 18.12.2024.
Keywords: meat steaks; beef; marinating; intensification; organoleptics; marinating channels; improvement